Ergonomic assessment of manual building work associated with lifting tasks/Rankų darbo statyboje, keliant mažagabaričius sunkius elementus, ergonominis vertinimas - Kaminskas, Kazys Algirdas (Journal of Civil Engineering and Management, 2001)
The purpose of these studies is to reduce the amout of low back pain as well as work injuries. Low back pain is more likely to occur if the load exceeds the worker's physical capabilities. In this paper, biomechanical criterion was based on calculating the compressive forces in the L5/S1 disc (Eqs (1), (2)).Three types of activity were taken into consideration. First, manual lifting granite plates (500× 500× 100 mm) with and without special devices (Figs 1, 2). Second manual lifting porous silicate blocks (300 × 600 × 200 mm). Third, manual lifting silicate brick in stooped postures.The investigation results presented in Fig 6 show clear benefits of ergonomic solutions for manual lifting heavy construction elements.The risk for back injuries becomes quite insignificant when ergonomic lifting devices are used (Fig 6 point f and g). These devices do not reduce the weight of lifted elements, but in case of a pneumatic device the total lifting weight is considerably increased, but the positive effect is achieved due to reducing moments because workers perform the task with a straight back.The reloaders of bricks usully feel back pain due to extreme repetitive bending of the back.First Published Online: 30 Jul 2012